KARAKTERISTIK FISIKOKIMIA MINYAK BIJI KELOR (Moringa oleivera L.) - Julianus Dising; Paulus Pasau (Partner, 2021)
In this study, moringa seeds extracted for oil were extracted from Kupang, East Nusa Tenggara. Moringa seed oil is obtained by extraction using n-hexane solvents. The extraction method used is the Soxhletasi method at a temperature of 68 oC, and is further separated between the solvent and its oil using rotavapor. Moringa seed oil obtained further characterized its physical and chemical properties. Characterization of the physical and chemical properties of moringa seed oil includes density, viscosity, saponification number, iodine number, acidic number, and peroxide number. The results showed that moringa seeds contained 28.6% oil. For testing of physical parameters of moringa seed oil obtained density of 0.912 g/ml, and viscosity of 1,054 cps. For testing chemical parameters obtained saponification number 18.65, acid number 132.42, iodine number 66.46, and peroxide number 6.8 meg/kg Key Words: moringa seed oil, extraction, characterization, fatty acids, peroxides